iTRAQ-based proteomics analysis of Bacillus pumilus responses to acid stress and quorum sensing in a vitamin C fermentation system - Zhang, Qian; Lyu, Shuxia (Frontiers in Microbiology, 2023)
Microbial consortia play a key role in human health, bioenergy, and food manufacturing due to their strong stability, robustness and versatility. One of the microbial consortia consisting of Ketogulonicigenium vulgare and Bacillus megaterium for the production of the vitamin C precursor, 2-keto-L-gulonic acid (2-KLG), has been widely used for large-scale industrial production. To further investigate the cell-cell communication in microbial consortia, a microbial consortium consisting of Ketogulonicigenium vulgare and Bacillus pumilus was constructed and the differences in protein expression at different fermentation time points (18 h and 40 h) were analyzed by iTRAQ-based proteomics. The results indicated that B. pumilus was subjected to acid shocks in the coculture fermentation system and responded to it. In addition, the quorum sensing system existed in the coculture fermentation system, and B. pumilus could secrete quorum-quenching lactonase (YtnP) to inhibit the signaling pathway of K. vulgare. This study offers valuable guidance for further studies of synthetic microbial consortia.